2000
DOI: 10.1128/mcb.20.17.6476-6482.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Rad51 Paralog Rad51B Promotes Homologous Recombinational Repair

Abstract: The highly conserved Saccharomyces cerevisiae Rad51 protein plays a central role in both mitotic and meiotic homologous DNA recombination. Seven members of the Rad51 family have been identified in vertebrate cells, including Rad51, Dmc1, and five Rad51-related proteins referred to as Rad51 paralogs, which share 20 to 30% sequence identity with Rad51. In chicken B lymphocyte DT40 cells, we generated a mutant with RAD51B/ RAD51L1, a member of the Rad51 family, knocked out. RAD51B؊/؊ cells are viable, although sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
186
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(209 citation statements)
references
References 67 publications
(101 reference statements)
20
186
3
Order By: Relevance
“…In this regard, HR seems to repair this type of DNA damage efficiently during S to G2 phase. Indeed, hypersensitivity to cross-linking reagents is a consistent feature of HR repair in deficient mutants described in vertebrate cell lines (Liu et al, 1998;Takata et al, 2000;Sasaki et al, 2004). Furthermore, a recent study reported that the Arabidopsis mutant with impaired Xrcc3, which is the interaction partner of AtRad51C (Osakabe et al, 2002), also shows hypersensitivity to the cross-linking reagent .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, HR seems to repair this type of DNA damage efficiently during S to G2 phase. Indeed, hypersensitivity to cross-linking reagents is a consistent feature of HR repair in deficient mutants described in vertebrate cell lines (Liu et al, 1998;Takata et al, 2000;Sasaki et al, 2004). Furthermore, a recent study reported that the Arabidopsis mutant with impaired Xrcc3, which is the interaction partner of AtRad51C (Osakabe et al, 2002), also shows hypersensitivity to the cross-linking reagent .…”
Section: Discussionmentioning
confidence: 99%
“…8 Repair of DNA double-strand breaks during the G1/S and S/ G2 phases of the mitotic cell cycle occurs through 2 main mechanisms, non-homologous end-joining and homologous recombination. [11][12][13] Of these, the homologous recombination is an error-free repair mechanism and its proper function is critical for maintaining the chromosomal integrity. 12 BRCA2 functions in homologous recombination together with RAD51 recombinase and colocalizes to the sites of DNA damage.…”
mentioning
confidence: 99%
“…The BCDX2 complex binds to nicks of duplex DNA and exhibits ATPase activity in vitro. These results together with the observations that RAD51B [107,108], RAD51C [111], RAD51D [117], and XRCC2 [123] are required for proper formation of RAD51 foci, indicate that these proteins may function as a complex both in assembling the RAD51 complex and in the initial processing of the single-stranded DNA at the damaged sites. Another complex, with RAD51C and XRCC3, was originally detected with a yeast two-hybrid system and then with interaction of proteins expressed in baculovirusinfected insect cells [132][133][134], and then confirmed with human cells lines that express isotope-tagged XRCC3 or RAD51C proteins [135].…”
Section: Rad51 Paralogs In Animals and Plants: Rad51b Rad51c Rad51dmentioning
confidence: 70%
“…Mutant analysis of RAD51B in a chicken B lymphocyte DT40 cell line indicates that RAD51B is important for maintaining genome integrity and for homologous recombinational repair [107,108]. However, the rad51b mutant cell line is viable; although about 20% cells die after each division as a result of spontaneous chromosomal aberrations, indicating that RAD51B is required for repairing DNA breaks or damages under normal growth conditions.…”
Section: Rad51 Paralogs In Animals and Plants: Rad51b Rad51c Rad51dmentioning
confidence: 99%